Seismic Response Analysis of Plus-Shaped Building with Various Re-Entrant Corner Ratios Using Time History Approach - Ruhma, Devi Yusufi; Nindyawati, Nindyawati (Jurnal Fondasi, 2025)
The construction of high-rise buildings with irregular geometry has now become common due to land limitations and development demands. However, during an earthquake, irregular buildings are more susceptible to structural damage compared to regular buildings. Therefore, this article presents information related to the behavior of 13-story, plus-shaped buildings to seismic forces from the recorded accelerations of the Chuetsu-oki, Chi-Chi, Kise, and Tokachi-oki earthquakes. This study aims to determine how the variation of the re-entrant corner ratio will affect the behavior of the structure in response to these seismic forces so that the selection of the plus shape in structural planning can be taken into consideration. The method used in the analysis is experimental simulation, starting from data collection to earthquake analysis and structural response. The results show that the re-entrant corner ratio increases the torsion moment against the regular model by a maximum of 67,52% for a ratio of 0,22, by 162,64% for a ratio of 0,44, and by 106,41% for ratios of 0,36 (X-dir.) and 0,58 (Y-dir.). It means that as the re-entrant corner ratio increases, there is an amplification of the torsional moment, which leads to a worse re-entrant corner stress concentration. The shape of motion that occurs also becomes increasingly complex, involving both translational and torsional movements simultaneously. Meanwhile, the base shear value is influenced by the earthquake acceleration and structural response.